Improving Education and Prevention of HIV/AIDS Transmission Among Transgender Women Through Integrated Services at Lubuk Pakam Public Health Center, Deli Serdang Regency - Sirait, Reni Aprinawaty; Silaban, Maria (JURNAL PENGMAS KESTRA (JPK), 2025)
Transgender women are one of the key populations highly vulnerable to HIV/AIDS transmission due to risky sexual behaviors, limited access to friendly health services, and high levels of social stigma. To address this issue, a community service initiative was carried out at the Lubuk Pakam Public Health Center (Puskesmas), Deli Serdang Regency, aimed at increasing knowledge and preventive efforts related to HIV/AIDS among transgender women through educational approaches and integrated services. The methods included needs assessment through observation and interviews, development of locally relevant educational materials, interactive counseling sessions, voluntary HIV testing (VCT), and training for healthcare providers. A total of 25 transgender participants joined the education session, and 15 underwent VCT accompanied by pre- and post-test counseling. The results showed an average increase in knowledge of 35.4% based on pre-test and post-test scores. Additionally, an inclusive HIV service corner was established, and anti-stigma communication training was conducted for healthcare workers. This approach proved effective in enhancing community engagement and improving awareness of HIV prevention among transgender individuals. Success factors included the use of visual media, community-based education, local language delivery, and strong institutional support from the health center. These findings highlight the importance of replicating similar programs in other regions, involving community peer educators as key partners. Sustained, locally tailored education is essential for effective HIV/AIDS control among marginalized populations such as transgender women.